PENGARUH KEPERCAYAAN, KUALITAS PELAYANAN, MOTIVASI HEDONIS BELANJA TERHADAP MINAT BERTRANSAKSI MENGGUNAKAN APLIKASI LAZADA - gine das prena (Jurnal Ilmiah Akuntansi & Bisnis, 2019)
This study aims to examine the effect of trust, service quality, hedonic shopping motivation on the interest in transacting using lazada application. The population used in this study is community using lazada application. The method of data collection techniques used are questionnaires and documentation. The testing technique used is validation and reliability tests and uses data analysis techniques in the form of classic assumption tests and multiple linear regression tests.. The hypothesis in this study was tested using t test and f test. The results of the study showed that all variables were declared free of interference from existing classical assumptions.From the results of multiple linear regression test results f obtained Fcount of 17.665> Ftable of 2.60 then Ho is rejected and Hi is accepted means that simultaneously there is a positive and significant influence between variables of trust, service quality, hedonic shopping motive towards interest in using the lazada application. The partial test shows the results that all independent variables have a positive effect on the interest in transacting using the lazada application.Keywords : Trust, Service Quality, Hedonic Shopping Motivation, Interest in Transacting